2021
DOI: 10.1039/d1cp02891j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical assessments on the interaction between amino acids and the g-Mg3N2monolayer: dispersion corrected DFT and DFT-MD simulations

Abstract: The interaction of a few amino acids (AAs) with graphene-like magnesium nitride (g‒Mg3N2) monolayer has been investigated with density functional theory (DFT) simulations. The Mg site was found to cause...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Ganji and co-workers showed that optimization of each interaction can be used to optimize the entire system. 39 In our study, the same approach has been used to explore the Z144 –active site amino acid interactions. The model systems were relaxed initially to estimate the interaction energies.…”
Section: Resultsmentioning
confidence: 99%
“…Ganji and co-workers showed that optimization of each interaction can be used to optimize the entire system. 39 In our study, the same approach has been used to explore the Z144 –active site amino acid interactions. The model systems were relaxed initially to estimate the interaction energies.…”
Section: Resultsmentioning
confidence: 99%
“…We also check the influence of the dispersion interactions on structural optimization. [28][29][30][31] We take two configurations (with and without a strain) as examples, and reoptimize them by employing both Grimme DFT-D2 and Grimme DFT-D3 methods. For our negative-Poisson's-ratio systems, under a longitudinal compressive/tensile strain, the lateral width is the most important geometric parameter, and we find that the absolute values of variation ratios of the widths are all smaller than 1.3%, and most of them are smaller than 0.6%, compared with that of a conventional DFT method without dispersion correction (see the ESI †).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the accuracy of the current computational method, the interaction energy was calculated using the high-level quantum chemistry second-order Møller–Plesset (MP2) theory during the self-consistent field calculation. 24,25…”
Section: Calculation Detailsmentioning
confidence: 99%
“…To evaluate the accuracy of the current computational method, the interaction energy was calculated using the high-level quantum chemistry second-order Møller-Plesset (MP2) theory during the self-consistent field calculation. 24,25 A finite differences method is used to calculate the elastic stiffness tensor, with each atom displaced in each direction by AE0.01 Å, a plane wave cut-off of 1000 eV, and k-point sampling of 2 Â 2 Â 2. The band structure of the amino acids is calculated using the HSE06 hybrid functional.…”
Section: Calculation Detailsmentioning
confidence: 99%